Development and stability of candy in soursop mass - Diógenes Júnior, Armando Carlos; Almeida, Stefanie de Freitas; Oliveira, Emanuel Neto Alves de; Freitas, Pedro Victor Crescêncio de; Feitosa, Bruno Fonsêca; Souza, Rosane Liége Alves de (Ciência e Natura, 2022)
The objective was to develop and characterize candies in soursop mass, replacing sucrose partially with glucose syrup, and to evaluate the stability during 90 days of storage under different temperatures. Two formulations of candies were prepared with sucrose substitution by glucose syrup, as well as a standard sample with sucrose alone. They were heated and concentrated to 71 °Brix for packaging in polyethylene packages. Afterwards, the candies were stored at 10 and 20 °C in a Biochemical Oxygen Demand (BOD) incubator and 28.1 °C (ambient temperature) for 90 days. During storage, the physical-chemical analyzes were performed: water content, total solids, pH, total titratable acidity, total soluble solids, water content and activity. It wasverified that the storage conditions caused reduction of the values of water content and water activity, besides increasing the values of total solids, total soluble solids and Ratio for all samples and storage conditions. The determining factor for the stability and preservation of product characteristics was the storage temperature; Being 10 ° C the ideal temperature for a better preservation of the candies in the standard formulation and 20 ° C for the added formulations of glucose syrup.